The taxation of income and expenditure of trusts in South Africa - Sogoni, Zanele (Department of Commercial Law, 2014)
For many decades men have made provisions for their illegitimate children and mistresses by using secret trusts ' hiding their embarrassing secrets from their families and friends. Many politicians and other public figures have been known to transfer assets to a trustee to manage in secret in order to avoid conflict of interest. Businesses employ trusts to protect the interests of debenture holders, to manage pension funds and to create employee share purchase and management incentive schemes. Parents set up trusts to preserve funds for their children, others to support a religious or social cause. For decades the trust has been a key tool in estate planning for wealthier individuals and for a very long time trusts have been described as cosy vehicles for tax avoidance. But recently, as a result of the changes in the tax legislation, trusts have received some bad press.